Aortic Elasticity Evaluated by Pulsed Tissue Doppler Imaging of the Ascending Aorta in Different Diseases: A Systematic Review. (May 2021) - Ren, Manyi; Li, Xiuzhen; Xue, Minghua
Several methods have been applied for the evaluation of aortic elasticity. Pulsed tissue Doppler imaging of the ascending aorta is a noninvasive method applied for the evaluation of aortic elasticity in wide variety of diseases which are reviewed in this study. A comprehensive systematic literature search was carried out in November 2019 using the English databases including PubMed, Scopus, Science Direct, and Embase. All references of eligible articles and published reviews on tissue Doppler imaging were searched for relevant publications. Data were extracted according to predefined criteria (including country of study origin, patient population, number of patients in case and control groups, and results of aortic elasticity evaluation in the specific patient groups compared with controls). Two independent reviewers extracted the data, and the results were checked, compared, and edited by the third reviewer. No formal assessment of the statistics of the primary data was made. The results showed that decreased aortic elasticity is not only present in cardiovascular diseases but also can be identified in diseases of other systems that affect cardiovascular system.